The care and feeding of waspish widows - Waite, Olivia (Waite, Olivia. Feminine pursuits, 2020)
"When Agatha Griffin finds a colony of bees in her warehouse, it's the not-so-perfect ending to a not-so-perfect week. Busy trying to keep her printing business afloat amidst rising taxes and the suppression of radical printers like her son, the last thing the widow wants is to be the victim of a thousand bees. But when a beautiful beekeeper arrives to take care of the pests, Agatha may be in danger of being stung by something far more dangerous...Penelope Flood exists between two worlds in her small seaside town, the society of rich landowners and the tradesfolk. Soon, tensions boil over when the formerly exiled Queen arrives on England's shores--and when Penelope's long-absent husband returns to Melliton, she once again finds herself torn, between her burgeoning love for Agatha and her loyalty to the man who once gave her refuge. As Penelope finally discovers her true place, Agatha must learn to accept the changing world in front of her. But will these longing hearts settle for a safe but stale existence or will they learn to fight for the future they most desire?"--Provided by publisher.